Optical solitons for the Kundu-Eckhaus equation with time dependent coefficient - İnç, Mustafa; Baleanu, Dumitru (Elsevier Gmbh, Urban & Fischer Verlag, 2018)
The first integral method (FIM) is applied to get the different type optical solitons of Kundu-Eckhaus equation (KE). A class of optical solitons of this equation is presented, and some of which are acquired for the first time. Constraint conditions guarantees existence of these solitons. It is illustrated that FIM is very effective method to reach the various type of the soliton solutions. (C) 2018 Elsevier GmbH. All rights reserved.
Keywords: FIM; Kundu-Eckhaus equation; Optical solitons